2007
DOI: 10.1507/endocrj.k06-143
|View full text |Cite
|
Sign up to set email alerts
|

Deterioration of Glycemic Control during Octreotide LAR Treatment in an Acromegalic Japanese Patient with Type 2 Diabetes Mellitus

Abstract: Abstract. We report a case showing deterioration of glycemic control during octreotide long-acting release (LAR) treatment in an acromegalic Japanese patient with type 2 diabetes mellitus. The patient did not show much improvement of insulin sensitivity (QUICKI; 0.33 before treatment, 0.35 during octreotide LAR treatment), and showed a significant reduction in early insulin secretion (insulinogenic index; 0.28 before treatment, 0.08 during octreotide LAR treatment) on 75 g oral glucose tolerance test (75gOGTT)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…However, predicting the onset of DM in acromegalic patients during somatostatin analog therapy remained difficult because of the diversity of insulin resistance/secretion in individuals. Kahara et al reported that a patient with octreotide LAR did not show an improvement in insulin sensitivity (QUICKI: 0.33 before treatment, 0.35 during octreotide LAR treatment) but did exhibit a reduction in insulin secretion (insulinogenic index: 0.28 before treatment, 0.08 during octreotide LAR treatment) [9]. The current patient exhibited IGT before octreotide LAR treatment and had a lower QUICKI than the patient in the study of Kahara et al, suggesting insulin resistance.…”
Section: Deterioration Of Dehydrationmentioning
confidence: 99%
“…However, predicting the onset of DM in acromegalic patients during somatostatin analog therapy remained difficult because of the diversity of insulin resistance/secretion in individuals. Kahara et al reported that a patient with octreotide LAR did not show an improvement in insulin sensitivity (QUICKI: 0.33 before treatment, 0.35 during octreotide LAR treatment) but did exhibit a reduction in insulin secretion (insulinogenic index: 0.28 before treatment, 0.08 during octreotide LAR treatment) [9]. The current patient exhibited IGT before octreotide LAR treatment and had a lower QUICKI than the patient in the study of Kahara et al, suggesting insulin resistance.…”
Section: Deterioration Of Dehydrationmentioning
confidence: 99%